Mapping the Global Adoption of Mandatory Vaccination against COVID-19: A Scoping Review - Jessica U. Damian; Takalani G. Tshitangano (MDPI AG, 2023)
The coronavirus (COVID-19) pandemic caused sicknesses ranging from mild to deadly, which disrupted lives and healthcare systems across the globe. Despite the availability of vaccines that are effective in significantly reducing the risks of death and severe disease, misperceptions of COVID-19 vaccine safety, efficacy, risks, and mistrust in institutions responsible for vaccination campaigns have been reported as factors contributing to vaccine hesitancy, leading to an unsatisfactory vaccination rate, which resulted in some countries implementing mandatory COVID-19 vaccination to increase vaccine uptake. This scoping review aimed at mapping global countries that have adopted mandatory COVID-19 vaccination and the reaction of citizens. PRISMA Extension for Scoping Reviews was used. Google Scholar was used to identify papers published in English from December 2019 to February 2022, irrespective of their methodology. A total of 140 studies were identified. After screening for duplication, access, and relevance, 24 were eligible for review. Approximately eleven countries implemented mandatory vaccination, mostly among healthcare workers. Citizens' reactions towards the policy varied, with some in support of the policy but with a preference for the healthcare workers, and some in support but with the condition that it will only apply to travel, schools, and shopping areas, while others rejected the policy. Studies that may be relevant but were excluded due to eligibility criteria may be a limiting factor to this study. Several ethical considerations should be explicitly addressed when evaluating whether mandatory COVID-19 vaccination is an ethically justifiable policy option as recommended by the WHO policy brief.